2012
DOI: 10.1371/journal.pone.0031835
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila as a Model for MECP2 Gain of Function in Neurons

Abstract: Methyl-CpG-binding protein 2 (MECP2) is a multi-functional regulator of gene expression. In humans loss of MECP2 function causes classic Rett syndrome, but gain of MECP2 function also causes mental retardation. Although mouse models provide valuable insight into Mecp2 gain and loss of function, the identification of MECP2 genetic targets and interactors remains time intensive and complicated. This study takes a step toward utilizing Drosophila as a model to identify genetic targets and cellular consequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…8C–D). Because dendritic defects in flight motoneurons alter flight performance (Vonhoff et al, 2012), we tested flight ability and found a significantly reduced flight response in adult D42> kat80 - IR versus wild type flies (Fig. 8F).…”
Section: Resultsmentioning
confidence: 99%
“…8C–D). Because dendritic defects in flight motoneurons alter flight performance (Vonhoff et al, 2012), we tested flight ability and found a significantly reduced flight response in adult D42> kat80 - IR versus wild type flies (Fig. 8F).…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila melanogaster were reared as previously described (Vonhoff and Duch, 2010;Vonhoff et al, 2012). Motoneuron GAL4 driver lines were: (1) w; P103.3-GAL4, UAS-mCD8-GFP;+, (2) C380-GAL4, UAS-mCD8-GFP;; Cha-GAL80 and (3) w;UAS-mCD8-GFP; D42-GAL4, Cha-GAL80.…”
Section: Animalsmentioning
confidence: 99%
“…UAS-hMECP2 and UAS-hR106W transgenic flies (Cukier et al, 2008; Vonhoff et al, 2012) were kindly provided by Dr. J Botas (Baylor College of Medicine, Houston, Texas). UAS-kibraRNAi on the X chromosome (Genevet et al, 2010) was obtained from the Vienna Drosophila Resource Center.…”
Section: Methodsmentioning
confidence: 99%
“…In patients and in mouse models both MECP2 loss- and gain- of function can cause changes in dendritic morphology (Armstrong, 2005; Cheng et al, 2014; Wang et al, 2013; Zhou et al, 2006). While there is no MECP2 ortholog in Drosophila , we recently found that expression of human MECP2 (h MECP2 ) severely reduces the dendritic complexity of identified Drosophila motoneurons while maintaining normal membrane currents (Vonhoff et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation